Social media and pharmacovigilance: A review of the opportunities and challenges. (2nd September 2015) - Sloane, Richard; Osanlou, Orod; Lewis, David; Bollegala, Danushka; Maskell, Simon; Pirmohamed, Munir
Abstract Adverse drug reactions come at a considerable cost on society. Social media are a potentially invaluable reservoir of information for pharmacovigilance, yet their true value remains to be fully understood. In order to realize the benefits social media holds, a number of technical, regulatory and ethical challenges remain to be addressed. We outline these key challenges identifying relevant current research and present possible solutions.